Effects of total coumarins from Pileostegia tomentella on exosomal miRNA expression and angiogenesis in colorectal cancer cells - Ying Liu; Dao-hai Cheng; Zheng-ying Su; Ji-hua Lv; Li Wang; Yu-yin Deng; Li Li (Taylor & Francis Group, 2024)
AbstractContext Pileostegia tomentella Hand. Mazz (Saxifragaceae) total coumarins (TCPT) show antitumour activity in colorectal cancer (CRC) with unknown mechanism of action. Tumour angiogenesis mediated by exosomes-derived miRNA exhibits the vital regulation of endothelial cell function in metastasis of CRC.Objective To investigate the effect of TCPT on exosomal miRNA expression and angiogenesis of CRC cells.Materials and methods HT-29-derived exosomes were generated from human CRC cells (HT-29) or either treated with TCPT (100 μg/mL) for 24 h, followed by identification by transmission electron microscope, nanoparticle tracking analysis (NTA) and Western blot. Co-culture experiments for human umbilical vein endothelial cells (HUVECs) and exosomes were performed to detect the uptake of exosomes in HUVECs and its influence on HUVECs cells migration and lumen formation ability. Potential target miRNAs in exosomes were screened out by sequencing technology. Rescue assays of angiogenesis were performed by the transfecting mimics or inhibitors of targeted miRNA into HUVECs.Results HT-29-derived exosomes, after TCPT treatment (Exo-TCPT), inhibited the migration and lumen formation of HUVECs, reduced the expression levels of vascular marker (FLT-1, VCAM-1 and VEGFR-2) in HUVECs. Furthermore, the level of miR-375-3p was significantly upregulated in Exo-TCPT. Rescue assays showed that high expression of miR-375-3p in HUVECs inhibited migration and lumen formation abilities, which was consistent with the effects of Exo-TCPT, whereas applying miR-375-3p inhibitors displayed opposite effects.Discussion and conclusion TCPT exhibits anti-angiogenesis in CRC, possibly through upregulating exosomal miR-375-3p. Our findings will shed light on new target exosomes miRNA-mediated tumour microenvironment and the therapeutic application of Pileostegia tomentella in CRC.